2020
DOI: 10.1016/j.ijans.2020.100256
|View full text |Cite
|
Sign up to set email alerts
|

Linking the Saudi Arabian 2030 vision with nursing transformation in Saudi Arabia: Roadmap for nursing policies and strategies

Abstract: The Saudi government is currently facing multiple challenges in achieving “The Gold Standard” in nursing practice. This is not limited to educational challenges, staffing shortage, paucity of international and national benchmark evidence, absence of clear and defined scope of nursing practice, and lack of appropriate policies and regulations. This study presented a comprehensive plan for developing a policy based on current challenges, recognition of policy goals, assessment of potential options and alternativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 28 publications
0
51
0
Order By: Relevance
“…However, it is reasonable to link these modest levels of work environment satisfaction with the current reported challenges in Saudi nursing practice. Per Alsufyani et al (2020), the status quo of nursing practice in Saudi Arabia is facing several challenges including shortage of staff, absence of clear and defined scope of practice, and lack of national and international benchmarking. Likewise, the findings showed that the study's participants ranked their communication satisfaction within KFMC as moderate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is reasonable to link these modest levels of work environment satisfaction with the current reported challenges in Saudi nursing practice. Per Alsufyani et al (2020), the status quo of nursing practice in Saudi Arabia is facing several challenges including shortage of staff, absence of clear and defined scope of practice, and lack of national and international benchmarking. Likewise, the findings showed that the study's participants ranked their communication satisfaction within KFMC as moderate.…”
Section: Discussionmentioning
confidence: 99%
“…However, this communication gap indicates a presence of centralized management which restricts communication, sharing in decision-making, and professional autonomy. Further, centralized management was also reported by Alsufyani et al (2020) as one of the challenges in nursing practice in Saudi Arabia. In addition, almost all of healthcare organizations in Saudi Arabia depend heavily on non-Saudi nurses from various nationalities with different native languages such as: English, Hindi, Malayic, Tagalog, Tamil, and Urdu.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Kingdom of Saudi Arabia (KSA), nurses of Saudi origin are in short supply and the government recruits many expatriate nurses (constitutes 50% of the nursing workforce in the KSA; Alboliteeh et al, 2017 ) to cover this shortage (Ministry of Health, 2018 ). In addition, the nursing profession in Saudi Arabia, which has faced a nursing shortage and challenges in the nursing work environment, has evolved since the development of the Vision 2030 programme that contributes to significant improvements in the areas of health delivery system, nursing, education, trade, communication, technology and science (Alsufyani et al., 2020 ). However, the demand for nurses in Saudi Arabia is expected to be more than double in the next 10 years, according to predictions (Alsufyani et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the nursing profession in Saudi Arabia, which has faced a nursing shortage and challenges in the nursing work environment, has evolved since the development of the Vision 2030 programme that contributes to significant improvements in the areas of health delivery system, nursing, education, trade, communication, technology and science (Alsufyani et al., 2020 ). However, the demand for nurses in Saudi Arabia is expected to be more than double in the next 10 years, according to predictions (Alsufyani et al., 2020 ). This means that 150,000 nursing positions will need to be filled by 2030 (Alsufyani et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%